An Unexpected Inactivation of N-Heterocyclic Carbene Organic Catalyst by 1-Methylcyclopropylcarbaldehyde and 2,2,2-Trifluoroacetophenone - Chen, Yanling; Lv, Jie; Pan, Xuling; Jin, Zhichao (Frontiers in Chemistry, 2022)
An unprecedented inactivation process of the indanol-derived NHC catalysts bearing N-C6F5 groups is reported. An unexpected multi-cyclic complex product is obtained from the 3-component reaction with the 1-methylcyclopropyl-carbaldehyde, the 2,2,2-trifluoroacetophenone and the NHC catalyst. The absolute structure of the inactivation product is unambiguously assigned via X-ray analysis on its single crystals. The formation of the structurally complex product is rationalized through a multi-step cascade cyclization process.